Pengaruh Kualitas Jasa Teknologi Informasi Terhadap Kepuasan Konsumen Dan Dampaknya Pada Loyalitas Mahasiswa Di Jurusan Non Rekayasa Politeknik Negeri Sriwijaya Palembang - Ida Wahyuningrum (Program Studi Magister Manajemen FE Unsri, 2011)
The State Polytechnic of Sriwijaya Palembang is trying to apply information technology in service quality to anticipate globalization that require inovation technology and information technology’s skills to doing bussiness by computer and internet where technology known as the key to reach competitive advantages. This research aimed to reveal how the direct effect of computer service quality and internet service quality on customers’s satisfaction, how the direct effect of customers’s satisfaction on customers’s loyalty, and how the indirect effect of computer service quality and internet service quality on customers’s loyalty by way of customers’s satisfaction in The State Polytechnic of Sriwijaya Palembang.This study used causal method. The respondents are 87 students of The State Polytechnic of Sriwijaya Palembang. The data collection techniques used are questionnaire and interviews. And then analyzed by using multiple linier regression with statistical product for special solution (SPSS) for windows version 15,0. This research result are: simultaneous, the computer service quality and internet service quality have direct effect on customer’s satisfaction by 48,8 percent. Partiality, computer service quality has direct effect on customer’s satisfaction by 30,7 percent and internet service quality has direct effect on customer’s satisfaction by 47,5 percent. Customers’s satisfaction has direct effect on customers’s loyalty by 34,percent. The computer service quality has indirect effect on customers’s loyalty for customers’s satisfaction by 41,3 percent and internet service quality has indirect effect on customers’s loyalty for customers’s satisfaction by 63,9 percent.Key words: computer service quality, internet service quality, customers satisfaction and customer loyalty.